Compliance security in the work of the HR service of an industrial enterprise - Veres Somosi, Mariann; Nagy, Szabolcs; Kobielieva, Tetiana (Хмельницький національний університет, 2024)
The report substantiates that the compliance security of the HR department of an industrial enterprise is a multifaceted process, including compliance with labor legislation, data protection, prevention of conflicts of interest and control over safety at workplaces. Compliance with compliance standards not only reduces legal and reputational risks, but also creates a favorable working environment for employees, contributing to the stable development of the enterprise.
Комплаенс-безопасность в работе HR-службы промышленного предприятия
Keywords: economic security; compliance; standards; norms; laws; financial stability